2019
DOI: 10.18203/2320-1770.ijrcog20191231
|View full text |Cite
|
Sign up to set email alerts
|

Waist hip ratio: an anatomical predictive marker of risk of PCOS

Abstract: Background: Polycystic ovarian syndrome (PCOS) is one of the most common endocrine disorders seen in infertility clinic of Gynae OPD. It is basically is disease of metabolic disorder and requires ultrasound and hormonal assay for its diagnosis.Methods: The study was carried out in the GOPD of MGM medical College and M.Y. Hospital Indore (M.P.) India. It included 200 women in the age group 18-40 years diagnosed as PCOS and who were compared with 200 women of same age group without PCOS. The height, weight BMI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
(8 reference statements)
3
4
3
Order By: Relevance
“…Conversely, no significant correlations were noted between vitamin D levels and age, BMI, reproductive hormones (progesterone, testosterone, estradiol, prolactin, AMH, TSH, FSH, LH, LH/FSH ratio), lipid profile (TC, HDL-C, LDL-C, TG, VLDL-C, LDL-HDL ratio), or insulin levels in either group (Table 3). group is in line with the clinical features typical of PCOS [2] and agrees with a previous report by Yadav and Tarware [16].…”
Section: Resultssupporting
confidence: 93%
“…Conversely, no significant correlations were noted between vitamin D levels and age, BMI, reproductive hormones (progesterone, testosterone, estradiol, prolactin, AMH, TSH, FSH, LH, LH/FSH ratio), lipid profile (TC, HDL-C, LDL-C, TG, VLDL-C, LDL-HDL ratio), or insulin levels in either group (Table 3). group is in line with the clinical features typical of PCOS [2] and agrees with a previous report by Yadav and Tarware [16].…”
Section: Resultssupporting
confidence: 93%
“…Yadav et al in their study reported the mean waist-hip ratio as 0.87±0.05 which was close to our study. 13 Interestingly, the association of PCOS and the waist hip ratio reached statistical significance in the study by Yadav et al unlike our study wherein statistical significance was not reached. This could be explained by the difference in total number of cases which was 60 in this study versus 400 in their study.…”
Section: Table 3: Distribution Of Subjects Based On Acnecontrasting
confidence: 80%
“…The mean age in this study for PCOS women was 22±3.9 years which was very close to the mean age of 23.26±3.56 years reported by Yadav et al in 2019. 13 However, earlier in 2017, Kumar et al in their study found the mean age of PCOS cases to be 28.6±6.3 years while Gul et al in 2018, found the mean age to be 26.7±7.54 years, higher than the mean age of this study. 14,15 This difference could be due to multiple factors explained as follows:…”
Section: Table 3: Distribution Of Subjects Based On Acnecontrasting
confidence: 62%
See 2 more Smart Citations